Hypercalcemia of malignancy - Raue, Friedhelm (Springer, 1994)
Hypercalcemia is the most common life-threatening metabolic disorder associated with cancer. The pathophysiological, epidemiological and clinical aspects of hypercalcemia of malignancy are presented in this issue, with a focus on the recently discovered humoral factor responsible for the development of hypercalcemia. With a better understanding of the pathophysiology of this condition and the development of new potent drugs, capable of inhibiting bone resorption, especially bisphosphonates, the clinician will be more successful in correcting hypercalcemia in the great majority of patients
Keywords: Aufsatzsammlung; Hyperkalzämie; Krebs